Truth-telling in cancer: Examining the cultural incompatibility argument in Turkey - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2010)
This article aims to examine critically the 'cultural incompatibility' argument, which asserts that disclosure of cancer-related information to patients is incompatible with Turkey's cultural context. For this purpose, a brief overview of the approach to truth-telling in Turkey will first be provided, followed by the claims of two different Turkish authors on the issue and a critical analysis of their approach. It will be contended that this argument has actually been formulated with paternalistic concerns and it may be playing an important role in shaping the approach of Turkish health care professionals to the issue. The article will then examine, in the light of study findings and case reports from Turkey, the concept of patient autonomy as it applies to truth-telling issues. It will be concluded that truth-telling can be compatible with Turkey's cultural context, provided that health care professionals place more emphasis on good communication with their patients.
Keywords: autonomy; cultural differences; cultural incompatibility; paternalism; truthful disclosure; truth-telling; PATIENT; NURSES; VIEWS